Dynamic media: music, video, animation, and the web in Adobe PDF - Connolly, Bob (Peachpit Press, 2006)
Flash animation, music and videos, virtual reality 3D, and more-in a PDF? Yes! Acrobat documents "converged" with audio, video, and interactive content- it's the wave of the future and it's called rich media. Do you want to get your video and audio content out into the world in a more convenient way than on the Web? Are you looking for a way to share rich-media content with the broadest possible range of readers? Print publishers, advertisers, educators, and anyone else who's ready to leverage the power of PDF and Adobe Reader can benefit from learning about the possibilities of this new convergence technology. In the first book of its kind, rich-media PDF pioneer Bob Connolly presents an eye-opening overview of the world of PDFs that contain video, audio, and interactive elements. Dozens of case studies illustrate the nearly limitless potential of rich media. And the best part about the book is that it practices what it preaches, with a fully interactive rich-media version of the book on the accompanying CDROM. Readers can experience first-hand the power of rich-media PDFs through interactive animation, videos, and audio. Walk through the process of constructing rich-media PDFs on the fly using a Web server Learn which applications work together for building rich-media PDFs-and which don't See how some of the world's most forward-thinking artists and designers are pushing the boundaries with rich-media PDFs Learn why PDF documents are more compelling than Web sites for reaching your target audience Understand how best to translate print material into online PDF documents.